Fostering spatial ability development in and for authentic STEM learning - Zhu, Caiwei; Leung, Chloe Oi-Ying; Lagoudaki, Eleni; Velho, Mariana; Segura-Caballero, Natalia; Jolles, Dietsje; Duffy, Gavin; Maresch, Günter; Pagkratidou, Marianna; Klapwijk, Remke (Frontiers in Education, 2023)
Empirical interdisciplinary research has explored the role of spatial ability in STEM learning and achievement. While most of this research indicates that fostering spatial thinking in educational contexts has the potential to positively impact students’ enrollment and performance in STEM subjects, there is less agreement on the best approach to do so. This article provides an overview of various types of effective spatial interventions and practices in formal or informal educational contexts, including targeted training of STEM-relevant spatial skills, spatialized curricula embedded in schools, integrated STEM practices addressing students’ use of spatial skills, and spatial activities in informal STEM education. Gender and socio-economic status of students – two variables that have been found to moderate the relationship between students’ spatial ability and their STEM performance – are also discussed in this article. Drawing on a wide spectrum of perspectives on situating spatial ability research in STEM education contexts, this article underscores the need for further inquiry into opportunities for developing K-12 students’ spatial ability through integrated and informal STEM practices. This article proposes a conjecture that the relationship between developing students’ spatial ability and enhancing their abilities to solve spatially complex STEM problems is bidirectional. Recommendations for future research are made on lingering questions about the effect of interventions, untapped resources for spatial ability training in formal and informal STEM education, and educational strategies for developing students’ spatial ability in authentic learning environments.